Konsep Hadis Optimis dengan Lisan dalam Perspektif Psikologi Islam (Studi Kasus pada Mahasiswi Sekolah Tinggi Dirasat Islamiyah Imam Syafi’i Jember): The Concept of Optimistic Verbally Hadith from an Islamic Psychology Perspective (Case Study on Students of Dirasat Islamiyah Imam Syafi'i Jember College) - Maimunah Nur Hadi; Salsabila Amatullah Zulfa; Septi Nuraini, Wahyu Griza; Nurul Intihan; Murtini, Nurul Budi (Pusat Penelitian dan Pengabdian masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, Indonesia, 2024)
Islam pays special attention to behavior, one of which is being optimistic when facing tests and trials from Allah Ta'ala. An optimistic attitude in Islam teaches that trials are a tool to lead to personal development in a better direction. Islamic psychology is a style of psychology based on the image of humans according to Islamic teachings. Imam Syafi'i Jember Dirasat Islamiyah College (STDI) is a Private Islamic Religious College (PTKIS), located in Sumbersari District, Jember Regency, East Java Province. The aim of this research is to find syarah, the concept of optimistic verbally hadith from an Islamic psychology perspective, as well as the implementation of verbally optimistic hadith in students at STDI Imam Syafi'I Jember. The research approach used in this research is a qualitative approach with a case study type. The results of this research show that (1) Optimistic verbally is an attitude recommended in Islam and has three concepts, (2) Optimistic verbally according to Islamic psychology, namely good words that are pleasant to hear and have a good influence on the soul of the listener and the spoken words can influence someone to do various good deeds, (3) Most of the informants have heard, know and understand the optimistic hadith verbally, then put it into practice.